Assessment of the State Forest Protection Management and Community Participation in the Central Highlands, Vietnam - Phan, Do Cao; Lan, Tran Thi (UI Scholars Hub, 2025)
This study focuses on state forest protection management in Central Highlands Vietnam, particularly in the Krong Bong District, Dak Lak Province, examining the role of community participation. The Central Highlands, a region rich in biodiversity and ecological significance, is severely impacted by deforestation, illegal logging, and land-use changes. This study assesses the current state of forest governance and proposes sustainable development improvement strategies. The research employs a mixed-methods approach, integrating secondary data, such as government reports and forest management reports from Krong Bong District, Đak Lak Province, as well as previous studies, with primary data collected from surveys of 96 forest managers and 60 households. The results show that forest management governance is organized but faces limited resources and overlapping responsibilities. The forest area increased from 65,054 hectares in 2019 to 68,740 hectares in 2022 due to reforestation efforts. However, rigid forest protection policies, limited community participation, inexperienced personnel, and over 1,100 forestry law violations between 2019 and 2022 underscore the challenges in law enforcement. This study signifies the crucial role of community engagement, which is still formally recognized as a weak part of forest protection management. It identifies the needs of community-based models that can ensure benefit-sharing, clear legal entitlements, and participatory planning processes, in coordination with government agencies and forest owners, to further prevent fragmented implementation.